Survival and Predictors of Mortality among Adults Initiating Highly Active Antiretroviral Therapy in Ethiopia: A Retrospective Cohort Study (2007-2019). (23rd November 2022) - Getaneh, Yimam; Ning, Feng; He, Qianxin; Rashid, Abdur; Kassa, Desta; Assefa, Yibeltal; Yi, Feng; Liao, Lingjie; Shao, Yiming
Abstract : Background . Studies have shown high early mortality after initiation of highly active antiretroviral therapy (HAART). We examined change in three-year survival and predictors of mortality of patients initiating HAART in Ethiopia since 2007 to 2019. Methods . A retrospective cohort study was conducted in 47 health facilities (HFs) using records of 11, 013 adult patients initiating HAART from 2007 to 2019. Study subjects were stratified as four different cohorts based on their calendar year of HAART initiation: 2007-2010, 2011-2013, 2014-2016, and 2017-2019. HFs were selected using probability proportional to size of patients. Survival rate and predictors of mortality were estimated by the calendar year using the Kaplan-Meier and Cox proportional hazard, respectively. We generated a pooled estimate of survival rate and predicators of mortality. Results . Data from 1881, 3868, 3004, and 2260 patients were retrieved from each of the cohorts. Overall mortality for all cohorts at all times was 10.3%. A gradual decline of mortality was observed in the first three years of follow-up since 2007-2016 which were 21.37%, 10.03%, and 4.34% among patients who initiated HAART in 2007, 2011, and 2014 respectively. A mortality jump of 9.25% was observed among patents initiating HAART in 2017, which coincided with political instability happened in the country. Of the 21, 638 person-years of follow-up among 11, 013 adults, mortality was 5.23/100 person-years, while disaggregated by the cohorts, it was 14.77, 5.06, 2.12, and 4.17 per 100 person-years, respectively. Among all the cohorts, patients with CD4 count of ≤200 cells/mm 3, unsuppressed viral load, poor adherence, and drug resistance in all cohorts, respectively, have overall 2.0 (95 % CI = 1.35 − 2.69 ), 4.66 (95 % CI = 2.53 − 6.72 ), 6.78 (95 % CI = 3.4 − 10.3 ), and 10.02 (95 % CI = 6.91 − 13.82 ) times of mortality risk than those without. Patients with bedridden for cohort initiating HAART during 2007 and 2011 were 2.0 (95 % CI = 1.35 − 2.69 ) times of mortality risk than those without. Conclusion . Patients initiating HAART from 2007 to 2016 have continuously improved their survival during three-year cohort follow-up in Ethiopia. The significant decline of survival among those who initiate HAART as of 2017 calls for program intervention. Low CD4 counts, unsuppressed viral load, poor adherence, and drug resistance could be used as predictors for increased mortality to monitor the quality of HAART and improve clinical management of HIV/AIDS patients.